2022
DOI: 10.1155/2022/8233269
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] The Ecological Consciousness of Natural Writing in British and American Romantic Literature

Abstract: The ecological crisis made the British and American ecological literature develop rapidly in the 20th century ecological thought. As a unique literary style that expresses the relationship between nature and man, British and American ecological literature has a far-reaching romantic tradition, and returning to nature is its eternal theme and dream. The study of the romantic tradition of British and American ecological literature has important implications for the development of ecological literature and ecolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…They explain the true meaning of beauty in nature, define the beauty of harmony with nature, promote getting back in touch with nature and the beauty of people, and expose a natural road that leads to truth, goodness, and beauty for those who are seeking their spiritual home. They also urged people to protect life and use natural resources responsibly while expressing their sincere concern for the environment and natural resources (Jin, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…They explain the true meaning of beauty in nature, define the beauty of harmony with nature, promote getting back in touch with nature and the beauty of people, and expose a natural road that leads to truth, goodness, and beauty for those who are seeking their spiritual home. They also urged people to protect life and use natural resources responsibly while expressing their sincere concern for the environment and natural resources (Jin, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%